2015
DOI: 10.7196/samj.8357
|View full text |Cite
|
Sign up to set email alerts
|

Integrated positron emission tomography/computed tomography for evaluation of mediastinal lymph node staging of non-small-cell lung cancer in a tuberculosis-endemic area: A 5-year prospective observational study

Abstract: Background. Integrated positron emission tomography/computed tomography (PET-CT) is a well-validated modality for assessing mediastinal lymph node metastasis in non-small-cell lung cancer (NSCLC), which determines management and predicts survival. Tuberculosis (TB) is known to lead to false-positive PET-CT findings. Objectives. To assess the diagnostic accuracy of PET-CT in identifying mediastinal lymph node involvement of NSCLC in a high TB-endemic area. Methods. Patients who underwent both PET-CT and lymph n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Fluorine 18 ( 18 F) fluorodeoxyglucose (FDG) combined positron emission tomography (PET) and computed tomography (CT) (hereafter, PET/CT) is based on the abnormally high rate of glucose metabolism found in cancer cells, and it is widely used in diagnostic imaging of many malignant tumors (3)(4)(5). Increased 18 F FDG uptake has been associated with poor prognosis in patients with HCC (6).…”
Section: Advances In Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Fluorine 18 ( 18 F) fluorodeoxyglucose (FDG) combined positron emission tomography (PET) and computed tomography (CT) (hereafter, PET/CT) is based on the abnormally high rate of glucose metabolism found in cancer cells, and it is widely used in diagnostic imaging of many malignant tumors (3)(4)(5). Increased 18 F FDG uptake has been associated with poor prognosis in patients with HCC (6).…”
Section: Advances In Knowledgementioning
confidence: 99%
“…Chen et al in several cancers (3)(4)(5). Investigators have reported that the sensitivity of 18 F FDG PET is low in the detection of HCC (12)(13)(14)(15), but the underlying mechanism for relatively low 18 F FDG accumulation in some patients with HCC is still unclear.…”
Section: Nuclear Medicine: Fbp1 Reduces 18 F Fdg Uptakementioning
confidence: 99%
“…[2] The majority of studies on PET-CT have been conducted in areas with a low or moderate prevalence of TB, a disease which is well known to cause false-positive results. [3,4] Developing regions, particularly TB-endemic areas, therefore face a potential challenge of interpreting PET-CT images as false positive. [5,6] The aim of this study was to assess the sensitivity, specificity, and diagnostic accuracy of integrated PET-CT in the evaluation of SPNs and masses in an area with a very high TB incidence.…”
mentioning
confidence: 99%
“…However, the PET-CT positive results required pathological verification, to exclude the potential possibility of tuberculosis. [ 25 ] Therefore, tuberculosis is known cause for to false-positive PET-CT findings. To enhance the control of tuberculosis in tuberculosis-endemic countries, such as India, Indonesia, China, and so on, may help improve the diagnostic accuracy of PET-CT in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Shaw et al reported that compared with a cut-off of 2.5, a SUV max cut-off of 4.5 yielded could promote the diagnostic accuracy from 64.0% to 84.7%. [ 25 ] Thus, to progress in tuberculosis control and optimize the standard of PET-CT technique may be promising approaches to reduce the false positive rate of PET-CT in lung cancer.…”
Section: Discussionmentioning
confidence: 99%